Correlation between HCN4 gene polymorphisms and lone atrial fibrillation risk - Xiao-Hong Li; Ya-Min Hu; Guang-Li Yin; Ping Wu (Artificial Cells, Nanomedicine, and Biotechnology, 2019)
Background and objective Atrial electrical remodelling (AER) was significantly associated with atrial fibrillation (AF) development. Polymorphisms in hyperpolarization activated cyclic nucleotide gated potassium channel 4 (HCN4) gene might be correlated with AER. In the present study, we explored the association of HCN4 polymorphisms (rs498005 and rs7164883) with lone AF risk in a Chinese Han population.Methods In this case–control study, the Sanger sequencing method was utilized to genotype the HCN4 polymorphisms. Relative risk of AF was assessed by the χ2 test, and presented by odds ratios (ORs) and corresponding 95% confidence intervals (CIs). Logistic regression analysis was performed for multivariate analysis. The effects of HCN4 polymorphisms on AF clinical features were analyzed by the Mann–Whitney U test and adjusted by the Bonferroni method.Results C allele of rs498005 was significantly correlated with increased risk of AF (OR = 1.412, 95%CI = 1.012–1.970), and the association still exited after adjustment by age, gender, the status of smoking and drinking, histories of diabetes, hyperlipidaemia and myocardial infarction (adjusted OR = 1.473, 95%CI = 1.043–2.081). G allele of rs7164883 SNP was marginally associated with enhanced AF risk after adjustment by the above clinical parameters (adjusted OR = 1.742, 95%CI = 1.019–2.980). Atrial late potential (ALP), including TP (P wave duration after filtering) and LP20 (the amplitude of superimposed potential in the final 20 ms of P wave) were significantly associated with rs498005 genotype (p < .001).Conclusion HCN4 rs498005 and rs7164883 polymorphisms are significantly associated with AF risk.